Measuring Exposure Opportunities: Using Exogenous Measures in Assessing Effects of Media Exposure on Smoking Outcomes - Liu, Jiaying (Commun Methods Meas, 2016)
Measurement of exposure has long been one of the most central and fundamental issues in communication research. While self-reported measures remain dominant in the field, alternative approaches such as exogenous or hybrid measures have received increasing scholarly attention and been employed in various contexts for the estimation of media exposure; however, systematic scrutiny of such measures is thin. This study aims to address the gap by systematically reviewing the studies which utilized exogenous or hybrid exposure measures for examining the effects of media exposure on tobacco-related outcomes. We then proceed to discuss the strengths and weaknesses, current developments in this class of measurement, drawing some implications for the appropriate utilization of exogenous and hybrid measures.